Employee Engagement and Organizational Trust in Millennial and Generation Z Employees: The Role of Psychological Well-Being Mediation and Transformational Leadership Perceptions in the Indonesian Formal Sector - Yustica Ilhamsyah, Destuwinny; Hayati, Neuneung Ratna (Journal Research of Social Science, Economics, and Management, 2026)
Low employee trust in organizations is a challenge for Millennials and Generation Z, who currently dominate the workforce. Various reports show that these two generations tend to have lower levels of organizational trust than previous generations, along with increasing expectations regarding the meaning of work, supportive work relationships, transparency, and empathetic leadership styles. However, previous studies have been limited in explaining the psychological mechanisms that link employee engagement to organizational trust in the context of the younger generation in Indonesia. This study aims to analyze the influence of employee engagement on organizational trust with psychological well-being and perceptions of transformational leadership as mediating variables among Millennial and Generation Z employees working in the formal sector. This study uses a quantitative approach with the PLS-SEM method on 207 respondents. The results show that employee engagement does not directly form organizational trust but has a significant effect through psychological well-being and perceptions of transformational leadership, which act as full mediators. These findings indicate that work engagement among the younger generation does not automatically build trust in the organization, but rather works through positive psychological experiences and perceptions of leadership quality. Practically, the results of this study emphasize the importance of managing employee engagement that is oriented towards strengthening psychological well-being and developing transformational leadership in order to build sustainable organizational trust.